Personality of I.F.Naumenko Through the Prism of His Epistolary - Khrystyna Kalahurka (Pedagogical Discourse, 2013)
Among the number of significant and objective sources for studying life, scientific and pedagogical activity of Fedor Ivanovych Naumenko, the famous Ukrainian educator of the 20th century, the epistolary is singled out. Correspondence is a significant part of the private archive of the scientist, which nowadays is kept in the department of manuscripts in Vasyl Stefanyk Lviv National Scientific Library of Ukraine and includes a number of valuable additions, generalizations, and clarifications. The epistolary heritage highlights family relationships of the scientist, complements his image as a personality and an educator, and reveals less known pages of his scientific cooperation. In particular, the correspondence highlights the role of F.Naumenko as a researcher and an expert in the Carpathian issues, and a consultant in issues of Makarenko-studies.